Inequality and injustices in the Anthropocene: Ecotheological perspectives on social justice, restoration, and forgiveness for peaceful coexistence - Denton, Rudy (Stellenbosch Theological Journal, 2025)
In the Anthropocene, human activities and ecological systems are deeply interconnected and mutually influence each other. However, human activity has become a dominant force, significantly impacting the entire biosphere and altering the balance of the Earth’s systems. This highlights the complex relationships between humans and non-human beings, as well as between humans and their diverse environments. Christian ecotheology has always viewed the ecological, economic, and social aspects of coexistence on Earth as being held together by the entire family of God (oikos/household). Exploring ecotheological perspectives on social inequality and injustices in the Anthropocene highlights the importance of social justice, restoration, and forgiveness as fundamental principles for peaceful coexistence among nations, countries, communities, and groups. This article advocates for a holistic approach to restorative justice and forgiveness that addresses inequality and injustice while fostering peaceful coexistence and promoting accountability, stewardship, sustainability, and care for the Earth.